PENGARUH NILAI TUKAR DAN HARGA EMAS TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA (Pasca Setahun Pelantikan Presiden) - Fadjar Harimurti, Teixa Lestari, Bambang Widarno & (Universitas Slamet Riyadi, 2016)
Stock price index is an indicator or reflection that shows the movement of stock prices. Index is used as a market trend. Weakened and the stock price index rising in a country could be due to economic conditions and economic performance in the country. After Ir. Joko Widodo sworn in as president, financial markets move higher. But after one year leadership of President Jokowi, the exchange rate and the price of gold fluctuated. It is also caused by the global economic slowdown. The purpose of this study was to analyze the effect of exchange rates and the price of gold antam the composite stock price index in the Indonesia Stock Exchange. The data used in this study is the closing times per week for 1 year after the presidential inauguration, namely October 2014 to October 2015. This study uses a simple linear regression analysis. The results of this method show that the exchange rate and the price of gold antam partially a significant negative effect on the stock price index in the Indonesia Stock Exchange. While the exchange rate positive and significant impact on the price of gold antam.Keywords: exchange rate, the price of gold, the stock price index